The Soviet mind : Russian culture under communism - Berlin, Isaiah, 1909-1997 (Brookings Institution Press, 2004)
Berlin (former professor of social and political theory, Oxford U., UK), well known for his political philosophy and its distinction between positive and negative freedoms, was less recognized as a Russian-Jewish migr . This collection of 10 essays gathers his writings on the USSR and includes his reflections on the work of Boris Pasternak and Osip.